Differential targeting of the dopamine transporter to recycling or degradative pathways during amphetamine‐ or PKC‐regulated endocytosis in dopamine neurons. Issue 8 (23rd April 2013) - Hong, Weimin C.; Amara, Susan G.
Abstract : The dopamine transporter (DAT) clears the extracellular dopamine released during neurotransmission and is a major target for both therapeutic and addictive psychostimulant amphetamines. Amphetamine exposure or activation of protein kinase C (PKC) by the phorbol ester PMA has been shown to down‐regulate cell surface DAT. However, in dopamine neurons, the trafficking itinerary and fate of internalized DAT has not been elucidated. By monitoring surface‐labeled DAT in transfected dopamine neurons from embryonic rat mesencephalic cultures, we find distinct sorting and fates of internalized DAT after amphetamine or PMA treatment. Although both drugs promote DAT internalization above constitutive endocytosis in dopamine neurons, PMA induces ubiquitination of DAT and leads to accumulation of DAT on LAMP1‐positive endosomes. In contrast, after amphetamine exposure DAT is sorted to recycling endosomes positive for Rab11 and the transferrin receptor. Furthermore, quantitative assessment of DAT recycling using an antibody‐feeding assay reveals that significantly less DAT returns to the surface of dopamine neurons after internalization by PMA, compared with vehicle or amphetamine treatment. These results demonstrate that, in neurons, the DAT is sorted differentially to recycling and degradative pathways after psychostimulant exposure or PKC activation, which may allow for either the transient or sustained inhibition of DAT during dopamine neurotransmission.—Hong, W. C.Amara, S. G., Differential targeting of the dopamine transporter to recycling or degradative pathways during amphetamine‐ or PKC‐regulated endocytosis in dopamine neurons. FASEB J. 27, 2995–3007 (2013). www.fasebj.org